Dosimetric control of high energy EB - P. Panta, Przemysław; Głuszewski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2004)
The dosimetric control of industrial installations used for radiation sterilization of medical devices, tissue grafts, pharmaceuticals, cosmetics, herbs and spices, is in practice very much related to the monitoring system of accelerators used for medical purposes. The methods of measurement of high doses as used in radiation processing are similar to those applied in small dose dosimetry, in the radiation therapy, for example. On the basis of long-term experience in the operation of radiation installations at the Institute of Nuclear Chemistry and Technology (INCT) some fundamental methods of dosimetry of EB are discussed. Calorimetric dosimeters developed at the Institute of Nuclear Chemistry and Technology are very useful in practical applications and in terms of quality are equivalent to commercial calorimeters offered by renowned foreign laboratories. It is worth noting graphite quasi-adiabatic calorimeters as absolute dosimeters and “CD-02” dose reader for the control of routine film dosimeters, which was developed in the INCT. This reader can also be used for the measurement of average energy of accelerated electrons using a popular method based on aluminum wedge. The paper reports on the application of electron spin resonance (ESR) technique in l-alanine and bone dosimetry. Bone dosimetry was used for ex post evaluation of accidental overexposure of radiotherapy patients in Białystok Hospital, which happened in 2001. The active participation in the meetings of Radiation Protection Inspectors as well as long-term cooperation of the INCT with the Tissue Bank of the Medical University of Warsaw in the field of radiation sterilization of allogenic grafts was an inspiration in this activity.